A Late Iron Age settlement in Wādī Banī Ḫālid: First season of the joint Omani‐Italian archaeological project. (30th October 2020) - Loreto, Romolo
Abstract: This paper introduces the first results of the joint Omani‐Italian archaeological project at Wādī Banī Ḫālid (northern Šarqiyyah governorate, eastern al‐Ḥaǧar), where a dense Iron Age and ancient Islamic occupation was detected. The aim of the project is the definition of the Iron Age settlement patterns along the eastern al‐Ḥaǧar landscape and its relationship with both the coastal areas and the al‐Ḥaǧar inner piedmont sites of central Oman. In fact, this project follows previous studies of the coastal environment between Muscat and Raʾs al‐Ḥadd, where several seasonal fishermen villages were investigated, and their connections with inner permanent sites, such as Lizq, recognised during the Early Iron Age II (1300–600 BCE). Therefore, Wādī Banī Ḫālid stands as a peculiar case of an Iron Age territorial unit, a natural scenario made of a narrow alluvial valley which provided natural conditions for the development of a complex culture. Moreover, the material culture emerged after a first excavation campaign proved that the main occupational phase of the imposing fortified settlement WBK1 is the Late Iron Age (late first millennium BCE to third–fourth centuries CE), thus hopefully allowing new questions to be posed for the definition of Late Iron Age cultures and the chronology in central Oman, which is mostly known based on the excavation of funerary evidence. For this reason, the first part of the paper focuses on the results of the first season in Wādī Banī Ḫālid, and the second part discusses the links between Wādī Banī Ḫālid and the south‐eastern Arabia general framework during the Late Iron Age.